Carbon crystal heating plate with excellent heat transfer characteristic and preparation method thereof
By setting a heat generating tube between the carbon crystal panel and the insulation cotton and filling it with high-performance heat-assisted adhesive, the problem of insufficient strength and heat transfer performance of the existing carbon crystal heating plate is solved, and higher heat transfer performance and strength are achieved , suitable for interior decoration of environmentally friendly furniture.
Patent Information
- Application Number
- CN202411643897.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
The coating strength and heat transfer performance of existing carbon crystal heating plates are low, resulting in poor strength and heat transfer performance.
By installing a heat generating tube between the carbon crystal panel and the insulation cotton, and filling a heat-supporting adhesive with high strength and heat transfer performance, the heat transfer performance and strength of the carbon crystal panel are improved.
The heat transfer performance and strength of the carbon crystal heating plate is improved, so that it can fully utilize the characteristics of large coverage area and good decorative effect in interior decoration, and also take into account the functions of heating and cooling to meet environmental protection requirements.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmentally friendly furniture, and in particular to a carbon crystal heating plate. Background Art
[0002] my country is rich in resources, and more and more boards are used for indoor temperature control. Among them, bamboo boards have uniform structure, and the surface patterns can be arbitrarily coated, and have good processing performance, so they are widely used in furniture manufacturing and construction industries. At present, the raw materials widely used in the preparation of fiberboards are cellulose and urea-formaldehyde resin. However, with the excessive felling of forest resources, how to ensure sufficient supply of cellulose raw materials has become an important problem facing the fiberboard manufacturing industry. In addition, urea-formaldehyde resin comes from non-renewable petrochemical resources, and it is easy to release free formaldehyde in a hot and humid environment, which seriously pollutes the environment and endangers human health. In addition, the above-mentioned boards used for indoor temperature control have low strength and low heat transfer performance.
[0003] The invention patent with the publication date of 2017-02-22 and the publication number of CN106455152A discloses a method for preparing a flame-retardant carbon crystal heating plate, including: 1) first fixing one end of the copper strip on the front of the first resin layer and extending the other end to the outside of the first resin layer; 2) then brushing graphite carbon slurry on the front of the first resin layer to form a graphite layer, and one end of the copper strip is coated in the graphite carbon slurry; 3) hot pressing the second resin layer on the graphite layer to obtain a sandwich panel; 4) hot pressing mica paper on both sides of the core panel, and naturally cooling to obtain a flame-retardant carbon crystal heating plate. The flame-retardant carbon crystal heating plate can generate heat evenly for a long time, has good high pressure resistance and heat resistance, and is safe to use. However, the strength and heat transfer performance of the graphite carbon slurry brushed in the invention patent are relatively low, resulting in the problem of poor strength and heat transfer performance of the manufactured carbon crystal heating plate. Summary of the invention
[0004] In view of the above technical problems, the present invention proposes a carbon crystal heating plate with excellent heat transfer characteristics and a preparation method thereof, which are used to solve the problem that the coating used in the carbon crystal heating plate in the prior art has low strength and heat transfer performance, resulting in poor strength and heat transfer performance of the manufactured carbon crystal heating plate.
[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows: A carbon crystal heating plate with excellent heat transfer characteristics comprises a carbon crystal plate and thermal insulation cotton bonded to the carbon crystal plate, a heating pipe is provided between the carbon crystal plate and the thermal insulation cotton, and a heat-assisting adhesive is filled between the carbon crystal plate, the heating pipe and the thermal insulation cotton. The present invention provides a heating pipe between the carbon crystal plate and the thermal insulation cotton to play a heating role, and fills a heat-assisting adhesive with high strength and heat transfer performance, thereby giving the carbon crystal plate heating and cooling characteristics while improving the heat transfer performance and strength, giving full play to the characteristics of the carbon crystal heating plate in interior decoration, such as large coverage area and good decorative effect, while taking into account the function of heating and cooling the decorative space. The addition of the heat-assisting adhesive makes the carbon crystal heating plate have uniform radiation heat transfer and fast defrosting, comfortable living environment, energy-saving operation, and the aluminum honeycomb core plate is formaldehyde-free and flame-retardant, which meets environmental protection requirements, and is energy-saving and environmentally friendly.
[0006] Furthermore, in order to make the adhesive have better bonding and combining capabilities, the thermal-assisting adhesive is formed by mixing an adhesive base material and a thermal-assisting material.
[0007] Furthermore, in order to enhance the heat transfer performance and strength of the binder, the binder base material includes silica sol, aluminum dihydrogen phosphate, kaolin, sodium hexametaphosphate and silane, and the thermal auxiliary material includes one or more of flake graphite, graphene, magnesium oxide powder, zinc powder, aluminum powder, aluminum ore powder and titanium powder.
[0008] Furthermore, the preparation method of the thermal adhesive comprises the following steps: A1. Place silica sol, aluminum dihydrogen phosphate solution, kaolin and sodium hexametaphosphate solution in a reaction kettle and fully emulsify; A2. The graphene and / or flake graphite and / or quartz sand are fully mixed and stirred to form a heat-assisting material; A3. Add silane to the mixture prepared in step A1 and stir thoroughly to allow the silane to be completely dispersed and then stop stirring to prepare a binder base; A4. Mix the heat-assisting material prepared in step A2 and the binder base material prepared in step A3 and stir thoroughly.
[0009] The production process of the heat-assisting adhesive of the present invention adopts room temperature emulsification, which not only reduces the production cost, but also improves the shelf life of the product and the stability of the product before curing during construction. In addition, heat-assisting materials such as graphene and / or flake graphite and / or quartz sand enhance the heat transfer performance and shear resistance of the heat-assisting adhesive.
[0010] Furthermore, in order to obtain a thermal-assisting adhesive with high cost-effectiveness and high heat transfer performance and strength, the silica sol uses silica sol containing 30% SiO2; the weight ratio of aluminum dihydrogen phosphate in the aluminum dihydrogen phosphate solution is 30%; the weight ratio of sodium hexametaphosphate in the sodium hexametaphosphate solution is 68%; the specification of kaolin is 300 mesh; the specification of the flake graphite is 200 mesh, the specification of the graphene is 3nm~7nm, the specification of the quartz sand is 200 mesh; and the silane uses KH550.
[0011] Furthermore, in order to further obtain a thermal-assistant adhesive with higher heat transfer performance and strength, the weight ratio of silica sol in the thermal-assistant adhesive is 26.3%~33.1%, the weight ratio of aluminum dihydrogen phosphate solution is 8.5%~26.3%, the weight ratio of sodium hexametaphosphate solution is 2.2%~6.3%, the weight ratio of kaolin is 2.7%~4.3%, the weight ratio of thermal-assistant material is 18.6%~56%, and the weight ratio of silane is 0.06%~1.2%.
[0012] Furthermore, in order to reduce production costs and improve the shelf life of the product and the stability of the product before curing during construction, the emulsification temperature of step A1 is 30°C~65°C, and the emulsification time is 50min~80min; the mixing and stirring temperature of step A4 is 30°C~70°C, and the mixing and stirring time is 10min~30min.
[0013] A method for preparing a carbon crystal heating plate with excellent heat transfer characteristics comprises the following steps: B1. Fix the bent heating tube on the carbon crystal plate; B2. Fill the heat-assisting adhesive between the heating tube and the carbon crystal plate, and apply the heat-assisting adhesive on the surface of the heating tube and the surface of the carbon crystal plate where there is no heating tube; B3, drying the semi-finished product coated in step B2; B4, bonding thermal insulation cotton to the coated surface in step B3.
[0014] Furthermore, the B1 comprises the following steps: B11. Decontaminate the surface of the bent heating tube and blow the carbon crystal plate to remove dust; B12. Use clamps to fix the heating tube on the carbon crystal plate.
[0015] Furthermore, the semi-finished product in step B3 is dried in a dry environment at a temperature of 45°C to 50°C for 6h to 8h; dried in a dry environment at a temperature of 25°C to 30°C for 10h to 12h; dried in a dry environment at a temperature of 10°C to 15°C for 18h to 24h.
[0016] Beneficial effects of the present invention: 1. The present invention forms a preliminary adhesive base material by premixing and pre-emulsification, and then adds a crosslinking agent silane, so that the adhesive base material has good bonding and combining capabilities, ensuring that the physical and mechanical properties of the prepared composite adhesive, i.e., the thermal adhesive, are good; 2. The heat-assisting material in the manufacturing process of the present invention adopts one or more of flake graphite, graphene, magnesium oxide powder, zinc powder, aluminum powder, aluminum ore powder, and titanium powder, which are fully mixed and emulsified and then mixed with aluminum dihydrogen phosphate solution, kaolin and sodium hexametaphosphate solution, thereby enhancing the heat transfer performance and shear resistance of the heat-assisting binder, and enhancing the energy storage performance and heat transfer performance of the aluminum honeycomb core plate; 3. The high shear strength heat-assisting adhesive of the present invention is produced by emulsification at room temperature and corresponding processes, which not only reduces the production cost, but also improves the storage period of the product and the stability of the product before curing during construction; 4. The present invention provides a heating pipe between the carbon crystal plate and the thermal insulation cotton to play a heating role, and fills a heat-assisting adhesive with high strength and heat transfer performance, thereby giving the carbon crystal plate the characteristics of heating and cooling, while improving the heat transfer performance and strength. It fully utilizes the characteristics of the carbon crystal heating plate in interior decoration, such as large coverage area and good decorative effect, while taking into account the function of heating and cooling the decorative space. The addition of the heat-assisting adhesive makes the carbon crystal heating plate have uniform radiation heat transfer and fast defrosting, making the living environment comfortable and energy-saving. The aluminum honeycomb core plate is formaldehyde-free and flame-retardant, which meets environmental protection requirements, and is energy-saving and environmentally friendly. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] The carbon crystal heating plate with excellent heat transfer characteristics described in the present invention comprises a carbon crystal plate and thermal insulation cotton bonded to the carbon crystal plate, a heating tube is arranged between the carbon crystal plate and the thermal insulation cotton, and a heat-assisting adhesive is filled between the carbon crystal plate, the heating tube and the thermal insulation cotton. In the process, the heating tube is first fixed on the carbon crystal plate, and then the heat-assisting adhesive is coated on the heating tube and the exposed carbon crystal plate, and then the environmentally friendly flame-retardant thermal insulation cotton is bonded on the coated surface with an environmentally friendly adhesive. The thermal-assisting adhesive is formed by mixing an adhesive base material with a thermal-assisting material. The present invention provides a heating pipe between the carbon crystal plate and the thermal insulation cotton to play a heating role, and fills a heat-assisting adhesive with high strength and heat transfer performance, thereby giving the carbon crystal plate heating and cooling characteristics while improving the heat transfer performance and strength. It fully utilizes the characteristics of the carbon crystal heating plate in interior decoration, such as large coverage area and good decorative effect, while taking into account the function of heating and cooling the decorated space. The addition of the heat-assisting adhesive makes the carbon crystal heating plate have uniform radiation heat transfer and fast defrosting, making the living environment comfortable and energy-saving. The aluminum honeycomb core plate is formaldehyde-free and flame-retardant, which meets environmental protection requirements and is energy-saving and environmentally friendly.
[0019] Furthermore, in order to enhance the heat transfer performance and strength of the binder, the binder base material includes silica sol, aluminum dihydrogen phosphate, kaolin, sodium hexametaphosphate and silane, and the thermal auxiliary material includes one or more of flake graphite, graphene, magnesium oxide powder, zinc powder, aluminum powder, aluminum ore powder and titanium powder.
[0020] Furthermore, the preparation method of the thermal adhesive comprises the following steps: A1. Place silica sol, aluminum dihydrogen phosphate solution, kaolin and sodium hexametaphosphate solution in a reaction kettle and fully emulsify; A2. The graphene and / or flake graphite and / or quartz sand are fully mixed and stirred to form a heat-assisting material; A3. Add silane to the mixture prepared in step A1 and stir thoroughly to allow the silane to be completely dispersed and then stop stirring to prepare a binder base; A4. Mix the heat-assisting material prepared in step A2 and the binder base material prepared in step A3 and stir thoroughly.
[0021] Furthermore, the silica sol uses silica sol containing 30% SiO2; the weight ratio of aluminum dihydrogen phosphate in the aluminum dihydrogen phosphate solution is 30%; the weight ratio of sodium hexametaphosphate in the sodium hexametaphosphate solution is 68%; the specification of kaolin is 300 mesh; the specification of the flake graphite is 200 mesh, the specification of graphene is 3nm~7nm, and the specification of quartz sand is 200 mesh; silane uses KH550, so as to obtain a thermal adhesive with high cost performance, heat transfer performance and strength.
[0022] Furthermore, the weight ratio of silica sol in the thermal adhesive is 26.3% to 33.1%, the weight ratio of aluminum dihydrogen phosphate solution is 15% to 26.3%, the weight ratio of sodium hexametaphosphate solution is 2.4% to 6.3%, the weight ratio of kaolin is 2.1% to 4.3%, the weight ratio of thermal material is 18.6% to 56%, and the weight ratio of silane is 0.06% to 1.2%, further obtaining a thermal adhesive with high heat transfer performance and strength. Among them, the weight ratio of graphene in the thermal material is 1.4% to 3.7%, the weight ratio of flake graphite is 11% to 37%, and the weight ratio of quartz sand is 6.2% to 15.3%.
[0023] Furthermore, the emulsification temperature of step A1 is 30°C to 65°C, and the emulsification time is 50min to 80min; the mixing and stirring temperature of step A4 is 30°C to 70°C, and the mixing and stirring time is 10min to 30min.
[0024] A method for preparing a carbon crystal heating plate with excellent heat transfer characteristics comprises the following steps: B1. Fix the bent heating tube on the carbon crystal plate; B2. Fill the heat-assisting adhesive between the heating tube and the carbon crystal plate, and apply the heat-assisting adhesive on the surface of the heating tube and the surface of the carbon crystal plate where there is no heating tube; B3, drying the semi-finished product coated in step B2 in a dry environment at a temperature of 45°C to 50°C for 6h to 8h; drying in a dry environment at a temperature of 25°C to 30°C for 10h to 12h; drying in a dry environment at a temperature of 10°C to 15°C for 18h to 24h; B4, bonding thermal insulation cotton to the coated surface in step B3.
[0025] Furthermore, the B1 comprises the following steps: B11. Decontaminate the surface of the bent heating tube and blow the carbon crystal plate to remove dust; B12. Use clamps to fix the heating tube on the carbon crystal plate.
[0026] The fixing member adopts the fixing member used for fixing the heating pipe in the prior art.
[0027] Example 1 Prepare silica sol containing 30% SiO2, aluminum dihydrogen phosphate solution containing 30% (by weight) aluminum dihydrogen phosphate, sodium hexametaphosphate solution containing 68% (by weight) sodium hexametaphosphate, kaolin with a specification of 300 mesh, flake graphite with a specification of 200 mesh, graphene with a specification of 5nm, quartz sand with a specification of 200 mesh, and KH550 as a silane crosslinking agent. And prepare the bent heating tube.
[0028] The thermal bonding agent is prepared by the following preparation method: S1. Place silica sol, aluminum dihydrogen phosphate solution, sodium hexametaphosphate solution and kaolin in a reaction kettle at a mass ratio of 32.4%, 26.3%, 2.5% and 2.1%, respectively, and fully emulsify at an emulsification temperature of 65°C and an emulsification time of 50 minutes; S2. 1.44% graphene, 24.57% flake graphite and 10.6% quartz sand were mixed and stirred for 20 minutes to form a heating material according to the mass ratio; S3. Add 0.09% by mass of silane crosslinker KH550 to the mixture prepared in step S1 and stir for 8 minutes to allow the silane to be completely dispersed and then stop stirring to prepare a binder base; S4. The heat-assisting material prepared in step S2 and the adhesive base material prepared in step A3 are mixed at a temperature of 50-60° C. and stirred for 20 minutes to form a finished heat-assisting adhesive.
[0029] Then the heating carbon crystal plate is prepared by the following preparation method: S5. Decontaminate the surface of the bent heating tube and blow the back of the carbon crystal plate to remove dust; S6. Place the heating tube on the back of the carbon crystal plate according to the design plan, and fix the heating tube on the carbon crystal plate with a clamp; S7. Fill the gap between the heating tube and the carbon crystal plate with the thermal adhesive prepared in step S4, and fill the heating tube and the carbon crystal plate with the thermal adhesive, and start applying the thermal adhesive from the top of the heating tube, with a coating thickness of 0.3mm. Trim the applied thermal adhesive from the top of the heating tube to the junction with the carbon crystal plate at the bottom to an approximate equilateral triangle, and continue to evenly apply 0.3mm of thermal adhesive on the carbon crystal plate along the bottom of the triangle with a spray gun or a splitting knife. The coating process of the thermal adhesive must be continuous until it is completely in contact with the bottom of the next heating tube to be qualified; the coating edge of the thermal adhesive in the area without the heating tube is not less than 80mm away from the heating tube, and if it is less than 80mm, it is coated to the edge of the carbon crystal plate. The coated semi-finished product is dried in a dry environment at 50°C for 8h; dried in a dry environment at 30°C for 12h; dried in a dry environment at 10°C for 24h; S8. Use environmentally friendly adhesive to bond 10mm thick environmentally friendly and odorless thermal insulation cotton that meets flame retardant requirements on the coated surface completed in S7 according to corresponding specifications.
[0030] Repeat the above steps to make multiple carbon crystal heating plates.
[0031] Example 2 Prepare silica sol containing 30% SiO2, aluminum dihydrogen phosphate solution containing 30% (by weight) aluminum dihydrogen phosphate, sodium hexametaphosphate solution containing 68% (by weight) sodium hexametaphosphate, kaolin with a specification of 300 mesh, flake graphite with a specification of 200 mesh, graphene with a specification of 7nm, quartz sand with a specification of 200 mesh, and KH550 as a silane crosslinking agent. And prepare the bent heating tube.
[0032] The thermal bonding agent is prepared by the following preparation method: S1. Place silica sol, aluminum dihydrogen phosphate solution, sodium hexametaphosphate solution and kaolin in a reaction kettle at a mass ratio of 28.3%, 23.44%, 2.4% and 3.1% respectively, and fully emulsify; the emulsification temperature is 50°C and the emulsification time is 60 minutes; S2. 1.6% graphene, 25.8% flake graphite and 15.3% quartz sand were mixed and stirred for 20 minutes to form a heating material according to the mass ratio; S3. Add 0.06% by mass of silane crosslinker KH550 to the mixture prepared in step S1 and stir for 8 minutes to allow the silane to be completely dispersed and then stop stirring to prepare a binder base; S4. The heat-assisting material prepared in step S2 and the adhesive base material prepared in step A3 are mixed at a temperature of 60-70° C. and stirred for 10 minutes to form a finished heat-assisting adhesive.
[0033] Then the heating carbon crystal plate is prepared by the following preparation method: S5. Decontaminate the surface of the bent heating tube and blow the back of the carbon crystal plate to remove dust; S6. Place the heating tube on the back of the carbon crystal plate according to the design plan, and fix the heating tube on the carbon crystal plate with a clamp; S7. Fill the gap between the heating tube and the carbon crystal plate with the thermal adhesive prepared in step S4, and fill the heating tube and the carbon crystal plate with the thermal adhesive, and start applying the thermal adhesive from the top of the heating tube, with a coating thickness of 0.3mm, trim the applied thermal adhesive from the top of the heating tube to the junction with the carbon crystal plate at the bottom to an approximate equilateral triangle, and continue to evenly apply 0.3mm of thermal adhesive on the carbon crystal plate along the bottom of the triangle with a spray gun or a splitting knife. The coating process of the thermal adhesive must be continuous until it is completely in contact with the bottom of the next heating tube to be qualified; the coating edge of the thermal adhesive in the area without the heating tube is not less than 80mm away from the heating tube, and if it is less than 80mm, it is coated to the edge of the carbon crystal plate. The coated semi-finished product is dried in a dry environment at 50°C for 6h; dried in a dry environment at 30°C for 10h; dried in a dry environment at 10°C for 24h; S8. Use environmentally friendly adhesive to bond 8mm thick environmentally friendly and odorless thermal insulation cotton that meets flame retardant requirements on the coated surface completed in S7 according to corresponding specifications.
[0034] Repeat the above steps to make multiple carbon crystal heating plates.
[0035] Example 3 Prepare silica sol containing 30% SiO2, aluminum dihydrogen phosphate solution containing 30% (by weight) aluminum dihydrogen phosphate, sodium hexametaphosphate solution containing 68% (by weight) sodium hexametaphosphate, kaolin with a specification of 300 mesh, flake graphite with a specification of 200 mesh, graphene with a specification of 3nm, quartz sand with a specification of 200 mesh, and KH550 as a silane crosslinking agent. And prepare the bent heating tube.
[0036] The thermal bonding agent is prepared by the following preparation method: S1. Place silica sol, aluminum dihydrogen phosphate solution, sodium hexametaphosphate solution and kaolin in a reaction kettle at a mass ratio of 26.3%, 15%, 6.3% and 4.3%, respectively, and fully emulsify at an emulsification temperature of 30°C and an emulsification time of 80 minutes; S2. 3.7% graphene, 37% flake graphite and 6.2% quartz sand were mixed and stirred for 20 minutes to form a heating material according to the mass ratio; S3. Add 1.2% by mass of the silane crosslinker KH550 to the mixture prepared in step S1 and stir thoroughly for 8 minutes to allow the silane to be completely dispersed and then stop stirring to prepare a binder base; S4. The heat-assisting material prepared in step S2 and the adhesive base material prepared in step A3 are mixed at a temperature of 30-40° C. and stirred for 30 minutes to form a finished heat-assisting adhesive.
[0037] Then the heating carbon crystal plate is prepared by the following preparation method: S5. Decontaminate the surface of the bent heating tube and blow the back of the carbon crystal plate to remove dust; S6. Place the heating tube on the back of the carbon crystal plate according to the design plan, and fix the heating tube on the carbon crystal plate with a clamp; S7. Fill the gap between the heating tube and the carbon crystal plate with the thermal adhesive prepared in step S4, and fill the heating tube and the carbon crystal plate with the thermal adhesive, and start applying the thermal adhesive from the top of the heating tube, with a coating thickness of 0.3mm, and trim the applied thermal adhesive from the top of the heating tube to the junction with the carbon crystal plate at the bottom to an approximate equilateral triangle, and continue to evenly apply 0.4mm of thermal adhesive on the carbon crystal plate along the bottom of the triangle with a spray gun or a splitting knife. The coating process of the thermal adhesive must be continuous until it is completely in contact with the bottom of the next heating tube to be qualified; the coating edge of the thermal adhesive in the area without the heating tube is not less than 100mm away from the heating tube, and if it is less than 100mm, it is coated to the edge of the carbon crystal plate. The coated semi-finished product is dried in a dry environment at 45°C for 8 hours; dried in a dry environment at 25°C for 12 hours; dried in a dry environment at 15°C for 18 hours; S8. Use environmentally friendly adhesive to bond 8mm thick environmentally friendly and odorless thermal insulation cotton that meets flame retardant requirements on the coated surface completed in S7 according to corresponding specifications.
[0038] Repeat the above steps to make multiple carbon crystal heating plates.
[0039] Example 4 Prepare silica sol containing 30% SiO2, aluminum dihydrogen phosphate solution containing 30% (by weight) aluminum dihydrogen phosphate, sodium hexametaphosphate solution containing 68% (by weight) sodium hexametaphosphate, kaolin with a specification of 280 mesh, flake graphite with a specification of 220 mesh, graphene with a specification of 3nm, quartz sand with a specification of 220 mesh, and KH550 as a silane crosslinking agent. And prepare the bent heating tube.
[0040] The thermal bonding agent is prepared by the following preparation method: S1. Place silica sol, aluminum dihydrogen phosphate solution, sodium hexametaphosphate solution and kaolin in a reaction kettle at a mass ratio of 33.1%, 26.3%, 6.3% and 4.3%, respectively, and fully emulsify; the emulsification temperature is 50°C and the emulsification time is 80 minutes; S2. 3.7% graphene, 11% flake graphite and 15.3% quartz sand were mixed and stirred for 20 minutes to form a heating material according to the mass ratio; S3. Add 1.2% by mass of the silane crosslinker KH550 to the mixture prepared in step S1 and stir thoroughly for 8 minutes to allow the silane to be completely dispersed and then stop stirring to prepare a binder base; S4. The heat-assisting material prepared in step S2 and the adhesive base material prepared in step A3 are mixed at a temperature of 30-40° C. and stirred for 30 minutes to form a finished heat-assisting adhesive.
[0041] Then the heating carbon crystal plate is prepared by the following preparation method: S5. Decontaminate the surface of the bent heating tube and blow the back of the carbon crystal plate to remove dust; S6. Place the heating tube on the back of the carbon crystal plate according to the design plan, and fix the heating tube on the carbon crystal plate with a clamp; S7. Fill the gap between the heating tube and the carbon crystal plate with the thermal adhesive prepared in step S4, and fill the heating tube and the carbon crystal plate with the thermal adhesive, and start applying the thermal adhesive from the top of the heating tube, with a coating thickness of 0.3mm, and trim the applied thermal adhesive from the top of the heating tube to the junction with the carbon crystal plate at the bottom to an approximate equilateral triangle, and continue to evenly apply 0.4mm of thermal adhesive on the carbon crystal plate along the bottom of the triangle with a spray gun or a splitting knife. The coating process of the thermal adhesive must be continuous until it is completely in contact with the bottom of the next heating tube to be qualified; the coating edge of the thermal adhesive in the area without the heating tube is not less than 100mm away from the heating tube, and if it is less than 100mm, it is coated to the edge of the carbon crystal plate. The coated semi-finished product is dried in a dry environment at 45°C for 8 hours; dried in a dry environment at 25°C for 12 hours; dried in a dry environment at 15°C for 18 hours; S8. Use environmentally friendly adhesive to bond 5mm thick environmentally friendly and odorless thermal insulation cotton that meets flame retardant requirements on the coated surface completed in S7 according to corresponding specifications.
[0042] Repeat the above steps to make multiple carbon crystal heating plates.
[0043] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that any modification to the technical solutions described in the aforementioned embodiments, or any equivalent replacement of some or all of the technical features therein, within the spirit and principles of the present invention, and such modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.
Claims
1. A carbon crystal heating plate with excellent heat transfer characteristics, characterized in that: It comprises a carbon crystal plate and thermal insulation cotton bonded to the carbon crystal plate, a heating tube is arranged between the carbon crystal plate and the thermal insulation cotton, and a heat-assisting adhesive is filled between the carbon crystal plate, the heating tube and the thermal insulation cotton.
2. The carbon crystal heating plate with excellent heat transfer characteristics according to claim 1, characterized in that: The heat-assisting adhesive is formed by mixing an adhesive base material and a heat-assisting material.
3. The carbon crystal heating plate with excellent heat transfer characteristics according to claim 2, characterized in that: The binder base material includes silica sol, aluminum dihydrogen phosphate, kaolin, sodium hexametaphosphate and silane, and the thermal auxiliary material includes one or more of flake graphite, graphene, magnesium oxide powder, zinc powder, aluminum powder, aluminum ore powder and titanium powder.
4. The carbon crystal heating plate with excellent heat transfer characteristics according to claim 3, characterized in that: The preparation method of the thermal bonding agent comprises the following steps: A1. Place silica sol, aluminum dihydrogen phosphate solution, kaolin and sodium hexametaphosphate solution in a reaction kettle and fully emulsify; A2. The graphene and / or flake graphite and / or quartz sand are fully mixed and stirred to form a heat-assisting material; A3. Add silane to the mixture prepared in step A1 and stir thoroughly to allow the silane to be completely dispersed and then stop stirring to prepare a binder base; A4. Mix the heat-assisting material prepared in step A2 and the binder base material prepared in step A3 and stir thoroughly.
5. The carbon crystal heating plate with excellent heat transfer characteristics according to claim 4, characterized in that: The silica sol uses silica sol containing 30% SiO2; the weight ratio of aluminum dihydrogen phosphate in the aluminum dihydrogen phosphate solution is 30%; the weight ratio of sodium hexametaphosphate in the sodium hexametaphosphate solution is 68%; the specification of kaolin is 280 mesh to 300 mesh; the specification of the flake graphite is 200 mesh to 220 mesh, the specification of graphene is 3nm to 7nm, and the specification of quartz sand is 200 mesh to 220 mesh; silane uses KH550.
6. The carbon crystal heating plate with excellent heat transfer characteristics according to claim 5, characterized in that: The weight ratio of silica sol in the thermal-assisting adhesive is 26.3% to 33.1%, the weight ratio of aluminum dihydrogen phosphate solution is 15% to 26.3%, the weight ratio of sodium hexametaphosphate solution is 2.4% to 6.3%, the weight ratio of kaolin is 2.1% to 4.3%, the weight ratio of thermal-assisting material is 18.6% to 56%, and the weight ratio of silane is 0.06% to 1.2%.
7. The carbon crystal heating plate with excellent heat transfer characteristics according to claim 6, characterized in that: The emulsification temperature of step A1 is 30°C to 65°C, and the emulsification time is 50min to 80min; the mixing and stirring temperature of step A4 is 30°C to 70°C, and the mixing and stirring time is 10min to 30min.
8. The method for preparing a carbon crystal heating plate with excellent heat transfer characteristics as claimed in any one of claims 4 to 7, characterized in that: The steps include: B1. Fix the bent heating tube on the carbon crystal plate; B2. Fill the heat-assisting adhesive between the heating tube and the carbon crystal plate, and apply the heat-assisting adhesive on the surface of the heating tube and the surface of the carbon crystal plate where there is no heating tube; B3, drying the semi-finished product coated in step B2; B4, bonding thermal insulation cotton to the coated surface in step B3.
9. The method for preparing a carbon crystal heating plate with excellent heat transfer characteristics according to claim 8, characterized in that: The B1 comprises the following steps: B11. Decontaminate the surface of the bent heating tube and blow the carbon crystal plate to remove dust; B12. Use clamps to fix the heating tube on the carbon crystal plate.
10. The method for preparing a carbon crystal heating plate with excellent heat transfer characteristics according to claim 8, characterized in that: The semi-finished product in step B3 is dried in a dry environment at a temperature of 45°C to 50°C for 6h to 8h; dried in a dry environment at a temperature of 25°C to 30°C for 10h to 12h; dried in a dry environment at a temperature of 10°C to 15°C for 18h to 24h.
Citation Information
Patent Citations
Bendable carbon crystal heating plate and manufacturing method thereof
CN106455152A